The Influence on Fracture Resistance of Different Composite Resins and Prefabricated Posts to Restore Endodontically Treated Teeth - Pamato, Saulo (2023)
Recent formulations of resin-based composites have incorporated different combinations of materials. However, the mechanical and bonding behavior of these materials with intraradicular posts are unclear. This study aimed to evaluate the effect of light-cure and dual-cure resin composite posts on the fracture resistance of endodontically-treated teeth. Materials and Methods: Ninety extracted human upper canines were selected and randomly divided into nine groups (n=10): (G1) endodontically treated teeth without endodontic posts; (G2) glass-fiber post cemented with glass-ionomer cement; (G3) endodontic post by dual-cure composite resin (Rebilda DC); (G4) endodontic post by dual-cure composite resin (Cosmecore); (G5) endodontic post by dual-cure composite resin (Bis-Core); (G6) endodontic post by light-cure composite resin; (G7) glass-fiber post customized with flowable composite resin; (G8) glass-fiber post cemented with light-cure composite resin; (G9) glass-fiber post cemented with self-adhesive resin cement. After the post insertion, all specimens were subjected to mechanical (250,000 cycles) and thermocycling (6000 cycles, 5 °C/55 °C) and immediate loading at 45 degrees in a universal testing machine until fracture. The data were analyzed by one-way ANOVA and multiple comparisons using the Fisher LSD Method (p < 0 05). Results: The mean failure loads (±SD) for the groups ranged from 100.7 ± 22.6 N to 221.9 ± 48.9 N. The G1 group (without endodontic posts) had a higher fracture strength than all experimental groups (p < 0.001). Conclusions: Within the limitations, the light- and dual-cure post technique did not present lower fracture resistance values as compared to the conventional glass-fiber post.